Leadership theory and the community college : applying theory to practice - Nevarez, Carlos, 1969-; Penrose, Rose (Stylus Publishing, 2013)
"This book presents leaders and aspiring leaders in community colleges with a theoretical and practical framework for analyzing their leadership styles, and determining the dimensions of leadership they need to improve in order to strengthen their capacity to resolve complex issues and effectively guide their institutions.